A familial case of Birt–Hogg–Dubé syndrome complicated with various cancers. Issue 4 (11th March 2020) - Goto, Yuki; Tobino, Kazunori; Munechika, Miyuki; Yoshimatsu, Yuki; Ide, Hiromi; Tsuruno, Kosuke
Abstract: An 89‐year‐old woman with small papules on her face presented to our hospital complaining of progressive dyspnoea. Chest computed tomography (CT) showed bilateral multiple lung cysts, a nodular opacity in the right lower lobe, and bilateral pleural effusion. She was diagnosed with adenocarcinoma. Her son, a 65‐year‐old man, also had bilateral basally located lung cysts and a past medical history of spontaneous pneumothorax. He had multiple papules on the face and neck, which were pathologically diagnosed as fibrofolliculomas. We considered these cases to be Birt–Hogg–Dubé syndrome (BHDS). Folliculin ( FLCN ) gene mutations that may be tumour suppressive are suspected to be causative of this syndrome. FLCN dysfunction might lead to the development of various types of tumours other than renal tumours. Abstract : Birt–Hogg–Dubé syndrome (BHDS) is a rare autosomal dominant inherited disorder characterized by fibrofolliculomas, renal tumours, lung cysts, and pneumothorax. This report described a familial case of BHDS complicated with various types of cancer (i.e. bladder, ureter, and lung).